SIDE EFFECTS THE DRUGS AND NUTRITIONAL STATUS OF THE BTA CONVERSION FAILURE IN LUNG TUBERCULOSIS PATIENTS - Henny Syapitri; Normi Parida Sipayung; Marthalena Simamora (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2015)
Introduction. The successful management of pulmonary TB can be seen by evaluating the results of treatment. Evaluation of the success in intensive phases of treatment visits and evaluation of bacteriological namely the conversion of BTA (+) sputum (-). This study aimed to analyze the infl uence of side effects the drugs and nutritional status of the BTA conversion failure. Methods. Types of analytical research with case control approach, which was done in Pulmonary Medicine Center of Medan. The study population consisted of the population, namely the case of patients who failed conversion of BTA (+) and a control population that patients with smear conversion (-) after undergoing intensive treatment phase. Samples in the case group were 32 cases and samples in the control group 64 cases. Data were analyzed by Chi-Square test. Result. Results showed variable drug side effects and signifi cantly affect the status of the failure of BTA conversion value (p = 0.022) and (p = 0.041). Discussion. Needs to be improved the ability of health workers to carry out the treatment of side effects the drugs by the availability of pharmaceutical preparations in order to side-effects that occur do not result in the cessation of the patient to take medication.Keywords: Side effects of drugs, nutritional status, conversion BTA